About Maps and Travels: a Story to Draw the Nation - Fernández Pérez-Sanjulián, Carme (Madrygal. Revista de Estudios Gallegos, 2020)
This paper analyzes the significance of the use of maps and routes through diverse territories in narrative and essay texts by Ramón Otero Pedrayo (Os camiños da vida, Arredor de si, Fra Vernero, A romeiría de Gelmírez, Devalar, Pelerinaxes I and newspapers and journals published in press). All of them show how the use of cartographic elements and the motive of travel serves the idea of consolidating a literary-cultural discourse embedded in a nationalist ideological project. At the same time, this project must be placed in the context of the continued work that the Galician intellectuals of this period develop to compete for influence in the public space.
Keywords: Ramón Otero Pedrayo; Maps; Travels; National Identity; Contemporary Galicien Literature